EFEKTIVITAS MEDIA PENYULUHAN YANG DIBERIKAN KEPADA PETANI KARET (Hevea brasiliensis) DI DESA GUNUNG BUNGSU KECAMATAN XIII KOTO KAMPAR (Studi Kasus Penyuluhan Pengendalian Jamur Akar Putih) - Nur Isnaini Abidin; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimed to analyze the effective extension of media used by farmers in the cultivation of rubber (Hevea brasiliensis) and goal attainment white root fungus control counseling viewed from the aspect of knowledge, attitude and skills of farmers in the village of Gunung Bungsu XIII Koto Kampar subdistrict, as well as analyzing media relations counseling towards the achievement of objectives in the Village of Gunung Bungsu extension XIII Koto Kampar subdistrict. The number of samples taken as many as 74 people from 14 farmer groups interviewed as respondents. Retrieval technique is purposive sampling of respondents. Data analysis was done descriptively and then converted to Likert Scale's Summated Rating (SLR) and Rank Spearman. The results showed that the use of agricultural extension media field (PPL) is more effective than the media leaflets and goal attainment extension as seen from the aspect of knowledge, attitudes and skills achieved enough. PPL media relations with the achievement of the objectives of extension seen from the aspect of knowledge has the power of a very strong relationship with a correlation value is 0,833 while media relations leaflet with the achievement of the objectives extension as seen from the aspect of knowledge has a low correlation with the strength of the correlation is 0,236. Key words: effectiveness, media outreach, rubbers farmer, and controlling white root fungus